Nanomaterials for Biomedical and Biotechnological Applications - Ferraro, Angelo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The need for constant improvement to reach a high standard of safety and to make nanomaterials accessible for marketing has generated a considerable number of scientific papers that highlight new important aspects to be considered, such as synthesis, stability, biocompatibility, and easy manipulation. In order to provide a comprehensive update on the latest discoveries concerning nanomaterials, this reprint presents 14 scientific papers, 10 research articles and 4 reviews, that deal with biomedical and biotechnological applications of nanomaterials.